Assessing self-efficacy and college readiness level among new undergraduate students in computer science using metacognitive awareness inventory (MAI) - Wan Nor Afiqah, Wan Othman; Aziman, Abdullah (IOP Publishing Ltd, 2018)
This preliminary study was conducted to address the issue of academic planning skills among new university student. Due to lack of proper measurement mechanism for awareness and readiness among students, this study proposes Metacognitive Awareness Inventory (MAI) to assess the connection between student self-efficacy and college readiness. Qualitative and quantitative approach were used by provide an online self-assessment for new student of Faculty of Computer Systems & Software Engineering (FSKKP) and analyse the data respectively. The possible relationships between MAI and College Readiness Item (CRI) in self-assessment has been evaluated. The sample size of 368 respondents from UMP are responding to the online self assessment. The initial finding shows most student (71%) of the respondent lack of skills in planning. We manage to use Pearson Product-moment correlation coefficient to find the significant relationship between MAI and CRI. Thus, we found that College Readiness provide sufficient evidence that there is a significant correlation with most of MAI items. The findings also indicated not much difference was found between gender in terms of self-efficacy level. This paper suggests the MAI and CRI is a reliable and valid scale to respond the planning skills issues among new university students.